2005
DOI: 10.2135/cropsci2003.0533
|View full text |Cite
|
Sign up to set email alerts
|

Genotype × Environment Interactions for a Diverse Set of Sweetpotato Clones Evaluated across Varying Ecogeographic Conditions in Peru

Abstract: whether to develop widely or specifically adapted genotypes and (ii) how to allocate resources between tests Sweetpotato [Ipomoea batatas (L.) Lam.] is cultivated across a for yield and nutritional traits. Such an understanding wide range of agrogeographical conditions. The objectives of this study were to analyze genotype ϫ environment (G ϫ E) interactions would also allow informed choices to be made regarding for sweetpotato yield (i.e., storage root yield, biomass, harvest index) which locations and input s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
93
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 113 publications
(125 citation statements)
references
References 19 publications
27
93
1
4
Order By: Relevance
“…Farmers pay particular attention to taste and quality traits before adopting a variety (Gruneberg et al 2005). Population means for starch were 53.2 % (120DAP), 59.0 (150DAP) and 56.9 % (180DAP) and consistent with previous findings of 56.3 to 64 % (La Bonte et al 2000;Brabet et al 1999).…”
Section: Discussionsupporting
confidence: 86%
“…Farmers pay particular attention to taste and quality traits before adopting a variety (Gruneberg et al 2005). Population means for starch were 53.2 % (120DAP), 59.0 (150DAP) and 56.9 % (180DAP) and consistent with previous findings of 56.3 to 64 % (La Bonte et al 2000;Brabet et al 1999).…”
Section: Discussionsupporting
confidence: 86%
“…In case of irregular rains-as they occur in Mozambique and other countries of southern Africa-there is limited knowledge whether it is possible to breed for sweetpotato clones which are adapted to drought and respond to rains adequately. Knowledge on the G 9 E structure is therefore important to facilitate recommendations for cultivar releases and to make informed choices regarding selection of cultivars with specific or wide adaptation in sweetpotato breeding programs (Grüneberg et al 2005). Storage root yield is influenced by various factors.…”
Section: Discussionmentioning
confidence: 99%
“…The genotype 9 environment interaction (G 9 E) significantly affect sweetpotato growth and productivity, as noted when testing bred-germplasm or cultivars under managed drought across sites in Kenya (Kivuva et al 2014), across locations in Mozambique (Henderson et al 1997) and Rwanda (Jannsens 1983), varying eco-geography in Perú (Grüneberg et al 2005), or across sites and over years in South Africa (Tekalign 2007). The G 9 E causes difficulty to selection of clones with wide adaptation, which may delay the cultivar release (Rukundo et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Sweetpotato is highly adapted to harsh environmental conditions. It was reported that significant genotype x environment interaction is present in sweetpotato in the root yield trait (Abidin et al, 2005;Grüneberg et al, 2005, Laurie, 2010 08. The location receives a total precipitation of 686 mm, and an average maximum and minimum temperature of 25.8°C and 10.5°C, respectively, during the growing season.…”
Section: Introductionmentioning
confidence: 99%